Probing the Stability of Fluorescent Proteins by Terahertz Spectroscopy - Xu, M. Y.; George, D. K.; Jimenez, R.; Markelz, A. G. (2014 39th International Conference on Infrared, Millimeter, and Terahertz Waves, 2014)
The higher transmission through tissues of long wavelength light motivates the development of fluorescent proteins with excitation shifted to the red. However red fluorescent proteins (RFPs) are more susceptible to photobleaching than their shorter wavelength counterparts. In particular RFPs are more susceptible to photobleaching [1]. A possible reason for this is a decrease in the structural stability of the beta barrel. Measurements of structural stability include atomic root mean squared displacement <x(2)> measured by the X-ray B-factor and neutron quasi elastic scattering. To date, X-ray measurements of RFP's do not indicate a structural stability change and systematic scattering studies have not been performed. Using THz dielectric response we examine if the picosecond structural flexibility decreases with increasing FP stability.
ISI Document Delivery No.: BF0IL Times Cited: 0 Cited Reference Count: 7 Cited References: Dean KM, 2011, BIOPHYS J, V101, P961, DOI 10.1016/j.bpj.2011.06.055 He YF, 2011, BIOPHYS J, V100, P1058, DOI 10.1016/j.bpj.2010.12.3731 Helms V, 2007, CHEMPHYSCHEM, V8, P23, DOI 10.1002/cphc.200600298 Leu BM, 2008, BIOPHYS J, V95, P5874, DOI 10.1529/biophysj.108.138198 Markelz AG, 2007, CHEM PHYS LETT, V442, P413, DOI 10.1016/j.cplett.2007.05.080 Nagy A, 2004, THERMOCHIM ACTA, V410, P161, DOI 10.1016/S0040-6031(03)00397-6 Zaccai G, 2000, SCIENCE, V288, P1604, DOI 10.1126/science.288.5471.1604 Xu, Mengyang George, D. K. Jimenez, R. Markelz, A. G. Irmmw-thz Proceedings Paper 39th International Conference on Infrared, Millimeter, and Terahertz waves (IRMMW-THz) Sep 14-19, 2014 Tucson, AZ THORLABS, Tydex, TOPTICA Photon, Bruker, Gentec EO, Lake Shore Cryotron, Ekspla, Zomega, TeraSense, Insight Product, Emcore, QMC Instruments, TeraView, NeaSpec, Advantest, MenloSystems, Traycer, Microtech Instruments Inc, LongWave Photon, Virginia Diodes Inc, ASU, MTT S, Journal Infrared Millimeter & Tera Hertz Waves, Tera Hertz Sci & Technol, Army Res Off George, Deepu/J-9882-2014 George, Deepu/0000-0003-0021-0705 345 e 47th st, new york, ny 10017 usa 2162-2027
Keywords: dynamics